Preparation method and system of coal cinder-based high-porosity sound-absorbing plate
Patent Information
- Application Number
- CN202611193866.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-30
AI Technical Summary
1、本申请在原料预处理阶段设置了磁场强度为0.3-0.5T的除铁处理和热处理温度为300-500℃的除碳处理。这种特定的预处理方式能够去除燃煤锅炉底渣中的铁磁性物质和残余碳。通过控制上述参数,排除了铁磁性杂质对后续发泡过程的干扰,防止了因残余碳分布不均导致的局部反应失控现象,为后续工序提供了成分稳定的原料,从而保证了最终吸声板材物理性能的稳定性。
Smart Images

Figure CN123003218A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of noise control materials, specifically relating to a method and system for preparing a high-porosity sound-absorbing panel based on coal slag. Background Technology
[0002] With the acceleration of industrialization, coal-fired power plants generate a large amount of coal-fired boiler ash. How to achieve the resource utilization of this industrial solid waste has become an important issue in the environmental protection field. Porous sound-absorbing materials are core functional materials in noise control engineering. Using coal-fired boiler ash to prepare sound-absorbing panels can not only consume a large amount of industrial solid waste but also meet the noise reduction needs of the building and transportation sectors. To achieve the transformation from waste ash to sound-absorbing panels, a complete preparation system is usually required, employing a series of crushing, mixing, molding, and curing equipment to transform scattered solid waste into building materials with a regular porous structure.
[0003] Existing systems for preparing sound-absorbing panels based on coal ash generally include basic raw material processing, batching, and molding / curing units. In a conventional production process, raw boiler bottom ash is finely ground using crushers and ball mills to obtain ash powder of a certain fineness, which is then stored in a batching silo. The subsequent process involves mixing the ash powder with cementitious materials, foaming agents, and various additives in a mixing mill according to specific ratios. The resulting slurry is then injected into molds for foaming or molded using pressing equipment. After curing in a conventional curing chamber or high-temperature kiln, it is finally formed into sound-absorbing panels.
[0004] The chemical composition and impurity content of bottom ash from coal-fired boilers are significantly affected by the type of coal and combustion conditions. The ash generally contains a certain amount of ferromagnetic substances and unburned residual carbon. In existing conventional processing procedures, ash powder containing ferromagnetic impurities directly enters the mixing and foaming stage, easily interfering with the chemical decomposition process of the foaming agent and affecting the uniform generation of internal bubbles. Randomly distributed residual carbon in the mixture can also lead to uneven intensity of local foaming reactions, easily causing localized runaway reactions. Conventional equipment lacks a targeted impurity removal pretreatment stage, making it difficult to precisely control the subsequent foaming and pore-forming process, resulting in uneven pore structure in the prepared sound-absorbing panels and a lack of stability in the physical properties of the final product. Summary of the Invention The purpose of this application is to provide a method and system for preparing high-porosity sound-absorbing panels based on coal slag, which can effectively solve the technical problems in the prior art, such as the difficulty in efficiently and effectively utilizing coal-fired boiler slag, the uncontrollable pore structure of sound-absorbing panels, unstable product performance, high production costs, and the difficulty in simultaneously meeting the requirements of sound absorption function and solid waste resource utilization.
[0005] To achieve the above objectives, the technical solution adopted in this application is as follows: a method for preparing a high-porosity sound-absorbing panel based on coal slag, comprising the following steps: Step 1: Finely grind the bottom ash of the coal-fired boiler to obtain ash powder. Then, the ash powder is subjected to iron removal treatment to remove ferromagnetic substances and carbon removal treatment to reduce carbon content. The ash powder after carbon removal treatment is dried and then screened to obtain boiler bottom ash powder. Step 2: Mix the boiler bottom ash powder with functional additives to obtain a mixture; the functional additives include at least a foaming agent; Step 3: The mixture is molded to obtain a sheet blank; Step 4: The plate blank is cured to finally obtain the coal slag-based high-porosity sound-absorbing plate; wherein, during the molding or curing process, the foaming agent releases gas to form a porous structure inside the mixture.
[0006] Preferably, in step one: the iron removal treatment is carried out using an iron removal device, and the magnetic field strength of the iron removal device is controlled at 0.3-0.5T; the carbon removal treatment is carried out using a carbon removal device, and the heat treatment temperature of the carbon removal device is controlled at 300-500℃.
[0007] Preferably, in step two: the functional additive further includes a cementing material and a foam stabilizer; after the functional additive is mixed with the boiler bottom ash powder, the mass ratio of each component is: 60%-80% boiler bottom ash powder, 15%-25% cementing material, 0.1%-1.0% foaming agent, and 0.05%-0.2% foam stabilizer; the operation sequence of mixing the boiler bottom ash powder with the functional additive is: first add the boiler bottom ash powder and the cementing material for premixing, and then add the foaming agent and the foam stabilizer for mixing.
[0008] Preferably, in step one: the bottom ash of the coal-fired boiler is fed into a crusher for coarse crushing, and then into a ball mill for fine grinding. The filling rate of the ball mill media is 30%-40%, and the specific surface area of the ash powder obtained after fine grinding is 3000-5000 cm² / g. The screening process is carried out using a multi-layer vibrating screen with screen apertures of 1 mm, 0.5 mm, and 0.15 mm respectively. The obtained boiler bottom ash powder has a particle size of 0.15-1 mm and a moisture content of less than 3%.
[0009] Preferably, in step three: water is added to the mixture, and a high-speed mixer is started for high-speed mixing. The mixing speed of the high-speed mixer is 1000-1500 r / min, and the mixing time is 3-5 min, so that the mixture forms a foam slurry. The foam slurry is injected into a casting mold for the molding process. After casting, the mold is left to stand and foam to obtain the board blank. In step four: the curing process involves sending the board blank together with the casting mold into a pre-curing chamber for pre-curing. After pre-curing, the board blank is demolded and transferred to a curing kiln for curing. After curing, the board blank is allowed to cool naturally.
[0010] Preferably, in step three: the temperature of the added water is controlled at 15-25℃, the pH value of the added water is controlled at 7-9, the temperature of the foam slurry is controlled at 20-35℃ during the high-speed stirring process, and the water-to-solid ratio of the added water to the mixture is controlled at 0.35-0.5; in step four: the pre-curing conditions are a temperature of 25℃ and a humidity greater than 90%, and the pre-curing time is 24h; when steam curing is carried out in the curing kiln, the steam pressure is controlled at 0.1-0.3MPa, the steam humidity is controlled at 95%-100%, and the heating rate is controlled at 2-5℃ / min.
[0011] Preferably, in step one: the bottom ash of the coal-fired boiler is fed into a fine grinding mill for fine grinding until the particle size of the ash powder is less than 0.075 mm, and the specific surface area of the ash powder obtained after fine grinding is 4000-6000 cm² / g; the moisture content of the ash powder after drying is less than 2%; in step two: the functional additive also includes a flux and a binder; after the functional additive is mixed with the boiler bottom ash powder, the mass ratio of each component is: 70%-80% boiler bottom ash powder, 5%-10% flux, 3%-5% binder, and 2%-5% foaming agent.
[0012] Preferably, in step three: water is added to the mixture, and the mixture after adding water is fed into a pressing and molding machine through a feeding device for pressing and molding. The pressing pressure is 15-25 MPa, the pressing number is 1-3 times, and the holding time is 30-60 s to obtain the plate blank; in step four: the curing treatment includes sending the plate blank into a drying chamber for drying, and then sending the dried plate blank into a high-temperature sintering furnace for sintering. The sintering process adopts a stepped heating regime: the heating rate from room temperature to 250℃ is 3℃ / min and held for 1 hour, the heating rate from 250℃ to 800℃ is 2℃ / min and held for 1 hour, the heating rate from 800℃ to 1100-1150℃ is 2℃ / min and held for 1-2 hours, and finally, it is naturally cooled to room temperature at a cooling rate of 2-5℃ / min.
[0013] A system for a high-porosity sound-absorbing panel based on coal ash includes a raw material pretreatment unit, a batching and mixing unit, a foaming and molding unit, and a curing and solidification unit connected in sequence. The raw material pretreatment unit receives the bottom ash from a coal-fired boiler and outputs the treated boiler bottom ash powder. The batching and mixing unit receives the boiler bottom ash powder and mixes it with a functional additive to output the mixture. The foaming and molding unit receives the mixture and generates a porous structure inside the mixture, molding and outputting the panel blank. The curing and solidification unit receives the panel blank and performs the curing treatment on the panel blank to output the high-porosity sound-absorbing panel based on coal ash.
[0014] Preferably, the raw material pretreatment unit includes an iron removal device, a carbon removal device, and a drying device; the iron removal device is installed before the drying device, and the magnetic field strength of the iron removal device is 0.3-0.5T; the carbon removal device is installed after the iron removal device, and the heat treatment temperature of the carbon removal device is controlled at 300-500℃.
[0015] Compared with the prior art, this application has the following beneficial effects: 1. This application incorporates iron removal treatment with a magnetic field strength of 0.3-0.5T and carbon removal treatment with a heat treatment temperature of 300-500℃ during the raw material pretreatment stage. This specific pretreatment method can remove ferromagnetic substances and residual carbon from the bottom ash of coal-fired boilers. By controlling the above parameters, interference from ferromagnetic impurities on the subsequent foaming process is eliminated, preventing localized runaway reactions caused by uneven distribution of residual carbon. This provides raw materials with stable composition for subsequent processes, thereby ensuring the stability of the physical properties of the final sound-absorbing board.
[0016] 2. This application controls the water-to-solid ratio within the range of 0.35-0.5 and the volume expansion rate of the foam slurry within the range of 2.5-4.0 times by controlling the process parameters during the mixing and foaming process. Combined with subsequent temperature and humidity curing management, a porous network consisting mainly of interconnected 0.1-2mm mesopores can be constructed within the board. This pore structure increases the air friction resistance during sound wave incidence, resulting in a sound-absorbing board with a porosity of 70% to 85%, achieving a compressive strength of over 3MPa while meeting the required mid-to-high frequency sound absorption coefficient.
[0017] 3. The preparation method of this application uses coal-fired boiler bottom ash as the main raw material, setting its mass proportion in the formula to 60% to 80%, and is compatible with both the non-fired cementitious foaming method and the high-temperature sintering method. Using a relatively high proportion of industrial solid waste as the base material reduces the reliance on conventional aggregates in traditional production, realizing the resource utilization of coal-fired solid waste. This allows the prepared porous board to possess multiple functions such as sound absorption, heat insulation, and Class A fire resistance, thereby reducing the overall production cost of sound-absorbing materials. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the overall technical solution architecture of the method for preparing high-porosity sound-absorbing panels based on coal slag proposed in this application; Figure 2 This is a schematic diagram of the core principle framework of the coordinated control of raw material pretreatment and precise parameters in this application; Figure 3 This is a flowchart of the main process framework for the non-fired gelation-foaming preparation method in this application; Figure 4 This is a schematic diagram of the stepped temperature-controlled sintering framework for the high-temperature sintering preparation process in this application. Detailed Implementation
[0019] To further illustrate the technical means and effects adopted by this application in order to achieve the intended purpose of the invention, the following detailed description of the specific implementation methods, structures, features and effects of this application is provided in conjunction with the accompanying drawings and preferred embodiments.
[0020] Example 1 like Figures 1-4 The present application provides a preparation system for a coal slag-based high-porosity sound-absorbing board, which includes a raw material pretreatment unit, a batching and mixing unit, a foaming and molding unit, and a curing and solidification unit.
[0021] The raw material pretreatment unit is used to perform steps S1, S2, and S3 in the independent method claims. Specifically, the crusher in the raw material pretreatment unit is used to perform the operation of feeding the bottom ash of the coal-fired boiler into the crusher for coarse crushing in step S1; the ball mill in the raw material pretreatment unit is used to perform the operation of feeding the coarsely crushed ash particles into the ball mill for fine grinding in step S1; the iron removal device and the carbon removal device in the raw material pretreatment unit are used to perform the operation of passing the finely ground ash powder through the iron removal device to remove ferromagnetic substances and the carbon removal device to reduce the carbon content in step S2; and the drying device and the screening device in the raw material pretreatment unit are used to perform the operation of passing the dried ash powder through the screening device to obtain boiler bottom ash powder with a particle size of 0.15-1 mm and a moisture content of <3% in step S3.
[0022] The batching and mixing unit is used to perform step S4 in the independent method claim; specifically, the metering feeder and dry mixer in the batching and mixing unit are used to perform the operation of adding boiler bottom ash powder to the dry mixer in proportion through the metering feeder in step S4, and adding cementitious material, foaming agent and foam stabilizer in proportion, first adding boiler bottom ash powder and cementitious material for premixing, and then adding foaming agent and foam stabilizer for mixing.
[0023] The foaming molding unit is used to perform steps S5 and S6 in the independent method claim; specifically, the high-speed mixer in the foaming molding unit is used to perform the operation of adding water to the dry mixing mixer and starting the high-speed mixer to perform high-speed mixing in step S5 so that the mixture forms a uniform foam slurry, and the casting mold in the foaming molding unit is used to perform the operation of injecting the foam slurry into the casting mold for molding and allowing it to stand in the mold for foaming in step S6.
[0024] The curing and curing unit is used to perform step S7 in the independent method claim; specifically, the pre-curing chamber and curing kiln in the curing and curing unit are used to perform the operation of sending the formed board together with the mold into the pre-curing chamber for pre-curing in step S7, demolding after pre-curing and transferring the board into the curing kiln for curing, and naturally cooling after curing.
[0025] This embodiment is specifically applied to the scenario of utilizing coal-fired power plant boiler slag to produce high-porosity sound-absorbing panels. In this scenario, the preparation system for high-porosity sound-absorbing panels based on coal slag works in synergy with the preparation method based on the non-fired cementitious-foaming process to achieve high-value utilization of industrial solid waste. The following details the specific structure of the system and how each unit collaboratively executes the steps in the independent claims.
[0026] The raw material pretreatment unit includes a crusher, a ball mill, an iron removal device, a decarbonization device, a drying device, and a screening device. The crusher's inlet receives the raw material, boiler bottom ash. The crusher is connected to the ball mill's outlet for coarse crushing of the boiler bottom ash. The ball mill's outlet is connected to the iron removal device's inlet, which in turn is connected to the decarbonization device's inlet. The decarbonization device's outlet is connected to the drying device's inlet, and the drying device's outlet is connected to the screening device's inlet. The crusher uses a jaw crusher or impact crusher, providing a large crushing ratio and uniform output particle size. A vibrating feeder is installed at the crusher's inlet to ensure uniform feeding and prevent large pieces of material from clogging the crusher. The ball mill can be either an intermittent ball mill or a continuous ball mill. The ball mill cylinder is filled with grinding media, which are steel balls or ceramic balls. The filling rate of the grinding media is 30%-40%. The filling rate refers to the proportion of the grinding media volume to the effective volume of the ball mill cylinder. Within this filling rate range, the ball mill efficiency is relatively high and the energy consumption is moderate.
[0027] The iron removal device employs a permanent magnet drum or electromagnetic separator, installed between the ball mill and the drying unit. The magnetic field strength of the iron removal device is controlled between 0.3-0.5T, calibrated and monitored using a Tesla meter. A magnetic field strength below 0.3T results in insufficient iron removal, while a strength above 0.5T significantly increases energy consumption and may adsorb non-ferromagnetic useful components. A buffer hopper is installed at the feed inlet to ensure uniform material flow through the iron removal zone, and a ferromagnetic material collection device is installed at the discharge outlet to collect removed ferromagnetic materials. The carbon removal device employs a flotation separator or heat treatment furnace, installed after the iron removal device. The heat treatment temperature is controlled between 300-500℃, reducing the loss on ignition to <8%. Heat treatment temperatures below 300℃ result in incomplete carbon combustion, while temperatures above 500℃ may damage the pozzolanic activity of the slag powder. When using a heat treatment furnace for decarbonization, an oxygen-rich environment should be maintained inside the furnace (e.g., an excess air coefficient controlled at 1.2-1.5). A temperature range of 300-500℃ ensures sufficient oxidation and combustion of unburned carbon particles while effectively preventing the active amorphous aluminosilicates in the slag from undergoing crystallization and losing their gelling activity. Alternatively, if a flotation separation tank is used for decarbonization, kerosene is used as the collector (1.5-3 kg / t slag), and 2-octanol is used as the frother (0.1-0.2 kg / t slag). The underflow slurry after flotation is filtered and then sent to a drying unit. The decarbonization unit is equipped with temperature sensors and atmosphere control devices to precisely control the heat treatment temperature and oxidizing atmosphere. The inlet and outlet of the decarbonization unit are equipped with sealing devices to prevent heat loss and the entry of outside air, which could affect the heat treatment effect.
[0028] The drying device employs either a fluidized bed dryer or a rotary drum dryer. A metering device is installed at the feed inlet to control the feeding speed. The drying temperature is controlled at 100-150℃, and the moisture content of the dried slag powder is controlled to be <2%. The drying device is equipped with temperature and humidity sensors to monitor temperature and humidity parameters in real time during the drying process. The screening device uses a multi-layer vibrating screen with at least three screen layers. The screen apertures, from coarse to fine, are 1mm, 0.5mm, and 0.15mm. Specifically, the first layer (1mm aperture) removes coarse particles larger than 1mm, the second layer (0.5mm aperture) removes intermediate particles (0.5-1mm), and the third layer (0.15mm aperture) removes fine particles (0.15-0.5mm) while retaining the target particle size range of 0.15-1mm. After screening, boiler bottom ash powder with a particle size of 0.15-1mm and a moisture content of <3% is obtained. The vibration frequency and amplitude of the vibrating screen are adjustable to adapt to different material characteristics. The discharge port of the vibrating screen is equipped with a quality detection device for online monitoring of the particle size distribution and moisture content of the powder.
[0029] Step 1: The bottom ash of the coal-fired boiler is fed into a crusher for coarse crushing, and then into a ball mill for fine grinding. The filling rate of the ball mill media is 30%-40%, and the specific surface area of the ash powder after fine grinding is 3000-5000cm² / g.
[0030] In the raw material pretreatment unit, the bottom ash of the coal-fired boiler is fed into the crusher for coarse crushing via a feeding device. The feeding device uses a vibrating feeder with a feeding speed of 5-15 t / h to ensure the crusher's processing capacity and crushing efficiency. The crusher applies impact and shear forces to the raw material, crushing large pieces into coarse particles with a diameter of 5-20 mm. The crushed slag particles are then conveyed into a ball mill for fine grinding. The ball mill applies a grinding action to the coarse particles, performing fine grinding with a ball mill media filling rate of 30%-40%. The ball mill speed is 60%-80% of the critical speed. The critical speed refers to the speed at which the grinding media begin to rotate with the ball mill cylinder without relative slippage. Within this speed range, the grinding media exert both impact and grinding effects, resulting in the highest fine grinding efficiency. During the fine grinding process, the ball mill cylinder rotates continuously, and the grinding media repeatedly impacts and rubs the slag particles, crushing them into a fine powder state. The specific surface area of the slag powder after fine grinding is 3000-5000 cm² / g. The specific surface area is determined by the Blaine permeability method. When the specific surface area is within this range, the slag powder has high pozzolanic activity and good molding performance.
[0031] Step 2: The finely ground slag powder is passed through an iron removal device to remove ferromagnetic substances and a carbon removal device to reduce the carbon content. After carbon removal, it is dried.
[0032] The finely ground slag powder is conveyed to an iron removal device for iron removal. The iron removal device applies a magnetic field to the slag powder, with the magnetic field strength controlled between 0.3-0.5T. Within this range, ferromagnetic materials are magnetically attracted to the surface of the magnetic rollers or plates of the iron removal device, while non-ferromagnetic materials flow out. The magnetic rollers or plates of the iron removal device rotate continuously, and the attracted ferromagnetic materials lose their magnetism after leaving the magnetic field area and fall into a ferromagnetic material collection device under gravity. The iron-removed slag powder is then conveyed to a decarbonization device for decarbonization. The decarbonization device heat-treats the slag powder at a temperature controlled between 300-500℃. Within this temperature range, residual carbon in the slag powder reacts with the introduced air or oxygen to produce carbon dioxide gas, which escapes, thus reducing the carbon content. The decarbonized slag powder is then conveyed to a drying device for drying at a temperature of 100-150℃. After drying, the moisture content of the slag powder is reduced to <3%.
[0033] Step 3: The dried slag powder is sieved through a screening device. The screening device is a multi-layer vibrating screen with screen apertures of 1mm, 0.5mm and 0.15mm respectively, so as to obtain boiler bottom ash powder with a particle size of 0.15-1mm and a moisture content of <3%.
[0034] The dried slag powder is conveyed to a screening device for sieving. The screening device uses a multi-layer vibrating screen. During operation, the vibrator generates periodic excitation force to drive the screen mesh to vibrate at a frequency of 1200-1800 times / min and an amplitude of 3-5 mm. After being fed into the vibrating screen, the slag powder passes through the screens layer by layer under vibration. The first screen has a 1 mm aperture; coarse particles larger than 1 mm are trapped on the first screen and discharged from the coarse particle outlet. These coarse particles can be returned to the ball mill for regrinding or disposed of for other purposes. Slag powder smaller than 1 mm passes through the first screen and falls to the second screen. The second screen has a 0.5 mm aperture; particles between 0.5 and 1 mm are trapped on the second screen and discharged from the middle particle outlet. These particles can be returned to the ball mill for regrinding. Slag powder smaller than 0.5 mm passes through the second screen and falls to the third screen. The third screen has an aperture of 0.15 mm. Particles with a diameter of 0.15-0.5 mm are trapped on the third screen and discharged from the fine particle outlet. Fine powder with a diameter smaller than 0.15 mm passes through the third screen and is discarded as sieved powder or disposed of for other purposes. Combining the separation results of each screen, boiler bottom ash powder with a particle size of 0.15-1 mm and a moisture content of <3% is obtained. This powder is discharged from the target particle size outlet of the vibrating screen and sent to the batching bin of the batching and mixing unit for temporary storage via a conveying device.
[0035] The batching and mixing unit includes multiple batching silos, a dry mixer, and a metering and feeding device. There are four batching silos, used to store boiler bottom ash powder, cementitious materials, foaming agents, and foam stabilizers, respectively. The cementitious materials are silicate cement or sulfoaluminate cement, which provide strength during the subsequent hydration reaction and form a synergistic cementitious system with the coal ash powder. The foaming agent is hydrogen peroxide or a surfactant, which decomposes upon contact with water, releasing gas to form bubbles. The foam stabilizer is calcium stearate or hydroxypropyl methylcellulose, which reduces the surface tension of bubbles and enhances the stability of bubble walls to prevent bubble coalescence and breakage. Specifically, when hydrogen peroxide is used as the foaming agent, a hydrogen peroxide aqueous solution with a mass concentration of 27.5%-35% is preferred. This concentration range ensures precise matching between the foaming rate and the initial setting time of the cementitious system, avoiding mold collapse or air trapping. When using surfactants, anionic surfactants such as sodium dodecyl sulfate (SDS) or sodium dodecylbenzene sulfonate (SDBS) are preferred. The silicate cement in the cementitious material is preferably ordinary silicate cement with a P·O42.5 grade or higher. The hydration product Ca(OH)2 of ordinary silicate cement can activate the pozzolanic activity of SiO2 and Al2O3 in the coal slag powder, generating CSH gel inside the pore walls. The reaction process of generating CSH gel is the core microscopic mechanism by which the sound-absorbing board obtained in this application maintains a compressive strength of over 3 MPa even with a high porosity of 70%-85%. Each batching bin is equipped with a metering feeder at its bottom. The metering feeder is a screw feeder or belt scale, connected to the inlet of the dry mixer to add the components measured according to the proportions into the dry mixer for mixing. The dry mixer has multiple spirally arranged mixing blades on its mixing shaft. When the mixing blades rotate, they push the material within the mixing drum, creating horizontal convection and vertical tumbling motions, ensuring thorough mixing of the material within the mixing drum. The mass ratio of each component is as follows: boiler bottom ash 60%-80%, cementitious material 15%-25%, foaming agent 0.1%-1.0%, and foam stabilizer 0.05%-0.2%. Within this ratio range, the cementitious material provides sufficient strength, coal ash powder serves as the main filler skeleton and active component, the foaming agent generates uniformly distributed bubbles, and the foam stabilizer ensures the stability of the bubbles. The feeding accuracy of the metering and feeding device is controlled within ±0.5% to ensure the accuracy of the proportions.
[0036] Step 4: Add the boiler bottom ash powder to the dry mixer according to the proportion using a metering feeder. At the same time, add the cementitious material, foaming agent and foam stabilizer according to the proportion. First, add the boiler bottom ash powder and cementitious material for premixing, and then add the foaming agent and foam stabilizer for mixing.
[0037] In the batching and mixing unit, the metering and feeding devices precisely measure each component according to the set ratio. The batching control logic first activates the first and second metering and feeding devices, respectively taking boiler bottom ash powder and cementitious material from their respective batching bins and adding them to the dry mixer. The addition rate of the boiler bottom ash powder and cementitious material is adjusted according to the processing capacity of the dry mixer. The mixing shaft of the dry mixer begins to rotate at a mixing speed of 80-120 r / min. Within this speed range, the material forms sufficient convective motion within the mixing drum but does not adhere to the drum wall due to excessive centrifugal force. After the first and second metering and feeding devices complete their feeding, the dry mixer continues to run for 3-5 minutes to ensure that the boiler bottom ash powder and cementitious material are fully premixed to form a uniform premixed powder. The bulk density of the premixed powder is 800-1200 kg / m³, and the moisture content is controlled at <1%. Under this moisture content condition, the premixed powder will not clump and the foaming agent will not react prematurely. Subsequently, the third and fourth metering feeders are activated, taking the foaming agent and foam stabilizer from their respective mixing bins and adding them to the dry mixer. During the addition process, the dry mixer continues to run, mixing for 3-5 minutes to ensure the foaming agent and foam stabilizer are evenly dispersed in the premixed powder. The final product is a homogeneous premixed powder with uniform distribution of components and no pre-activated foaming agent or foam stabilizer. This premixed powder is discharged through the outlet of the dry mixer and temporarily stored in the high-speed mixer of the foaming molding unit via a conveyor.
[0038] The foaming molding unit includes a high-speed mixer, a foam generator, and a casting mold. The high-speed mixer has a high-speed shearing head mounted on its mixing shaft. This head employs a multi-stage, interlocking blade structure and operates at a speed of 1000-1500 rpm to rapidly shear and mix the mixture after adding water, forming a uniform foam slurry. The foam generator is connected to the inlet of the high-speed mixer and uses a metering pump or electromagnetic flow meter to precisely control the water volume and water-to-solid ratio, maintaining the ratio precisely within the range of 0.35-0.5. The outlet of the high-speed mixer is connected to the inlet of the casting mold via a conveying pipe to inject the foam slurry into the mold for molding. The conveying pipe is made of wear-resistant and corrosion-resistant metal or plastic tubing with a smooth inner wall to reduce conveying resistance. The casting mold consists of an upper mold, a lower mold, and side molds. A cavity is formed between the upper and lower molds, and the shape of the cavity matches the finished shape of the sound-absorbing board. The side molds are detachably connected for easy demolding. A release liner with an anti-stick coating is installed inside the mold to prevent foam slurry adhesion. The volume expansion rate of the foam slurry is controlled at 2.5-4.0 times, the bulk density is 300-500 kg / m³, the flowability is 150-200 mm, the casting pressure is controlled at 0.01-0.05 MPa, and the casting speed is controlled at 0.5-1.5 kg / s. The pre-curing chamber and the curing kiln constitute the curing unit. The pre-curing chamber is equipped with temperature and humidity sensors and a spray device to maintain a curing environment of 25℃ and >90% humidity. A drainage trough is installed at the bottom of the pre-curing chamber to drain excess moisture generated during the curing process. The curing kiln is used for ambient temperature wet curing or steam curing. During steam curing, a flow regulating valve is installed on the steam pipeline to precisely control the amount of steam. The temperature and humidity control system is connected to the pre-curing chamber and the curing kiln respectively to monitor and adjust the temperature and humidity parameters of the curing environment in real time.
[0039] Step 5: Add water to the dry mixer, start the high-speed mixer for high-speed mixing at a speed of 1000-1500 r / min for 3-5 minutes, so that the mixture forms a uniform foam slurry.
[0040] In the foaming molding unit, the premixed powder taken from the premixed powder storage silo is fed into the high-speed mixer via a feeding device. The foam generator adds a measured amount of water to the high-speed mixer according to preset water-to-solid ratio parameters. The water temperature is controlled between 15-25℃. Too low a water temperature will reduce the reaction rate of the foaming agent and decrease foam stability, while too high a water temperature will cause the foaming agent to react too quickly and increase the risk of bubble coalescence and breakage. The pH value of the water is controlled between 7-9. Too low a pH value will cause the foaming agent to decompose prematurely, reducing foaming efficiency, while too high a pH value will cause the cementitious material to hydrate too quickly, affecting the stability of the foam slurry. The water-to-solid ratio is controlled between 0.35-0.5. When the water-to-solid ratio is below 0.35, the foam slurry is too viscous and difficult to flow and pour; when the water-to-solid ratio is above 0.5, the foam slurry is too thin and lacks sufficient strength development. The mixing shaft of the high-speed mixer begins to rotate at a speed of 1000-1500 r / min. Under the action of the high-speed rotating shearing head, water and premixed powder are thoroughly mixed to form a slurry. Simultaneously, the foaming agent undergoes a chemical reaction with the participation of water, releasing gas. The gas is dispersed into a large number of tiny bubbles by the shearing head and evenly distributed in the slurry, forming a foam slurry. During the mixing process, the temperature of the foam slurry is controlled between 20-35℃. Below 20℃, the foaming agent reaction is incomplete and the amount of bubble generation is insufficient; above 35℃, the bubble stability decreases and bubble merging and rupture may occur. The mixing time is 3-5 minutes. During this time, the bubble distribution in the foam slurry gradually becomes uniform and the bubble diameter stabilizes within the target range. The bubble diameter distribution of the foam slurry is 0.1-2 mm, with mesopores being the main component. The volume expansion rate of the foam slurry is controlled between 2.5-4.0 times. If the volume expansion rate is too low, the porosity is insufficient, affecting the sound absorption performance; if the volume expansion rate is too high, the stability of the foam slurry decreases and it is prone to collapse. The bulk density of the foam slurry is 300-500 kg / m³, and the fluidity is 150-200 mm. Within this parameter range, the foam slurry has good fluidity and stability, which facilitates subsequent casting and molding.
[0041] Step 6: Inject the foam slurry into the casting mold through the delivery pipe for molding. After casting, let it stand in the mold to foam.
[0042] After the foam slurry is prepared, the outlet of the high-speed mixer is opened, and the foam slurry is injected into the casting mold through the delivery pipe under its own gravity or by the action of the delivery pump. The casting pressure is controlled at 0.01-0.05MPa, and the casting speed is controlled at 0.5-1.5kg / s. Within this casting parameter range, the foam slurry flows smoothly in the mold cavity and gradually fills the entire cavity, avoiding the merging and rupture of air bubbles during the flow due to excessive casting pressure, and also avoiding uneven air bubble distribution caused by excessively high local pressure in the mold cavity due to excessively fast casting speed. The upper mold plate, lower mold plate, and side mold plate of the casting mold form a cavity that conforms to the shape of the finished sound-absorbing board. The mold is equipped with a release liner with an anti-stick treatment to prevent the foam slurry from adhering to the inner surface of the mold. After pouring, the pouring pipe is closed, and the foam slurry is allowed to stand in the mold for 10-30 minutes to foam. During this time, the foaming agent continues to decompose and release gas, causing the foam slurry to expand further and form a stable bubble structure. Simultaneously, the cementitious material begins an early hydration reaction, causing the foam slurry to gradually lose its fluidity and develop initial strength. The mold temperature is controlled at 20-30℃ during the standing foaming process. If the temperature is too low, the hydration reaction rate of the cementitious material is slow and foaming is incomplete; if the temperature is too high, the hydration reaction of the cementitious material is too rapid, which may destroy the bubble structure. After standing foaming, the foam slurry has formed a board blank with a porous structure, ready for subsequent curing and hardening processes.
[0043] Step 7: Send the formed board along with the mold into the pre-curing chamber for pre-curing. The pre-curing conditions are a temperature of 25℃ and a humidity of >90%. After pre-curing, demold the board and transfer it to the curing kiln for curing. After curing, allow it to cool naturally.
[0044] After molding, the slabs, along with the molds, are transported to a pre-curing chamber via a transfer device for pre-curing. The pre-curing chamber is a sealed room or box structure, equipped with temperature and humidity sensors and a spray system. The temperature and humidity sensors monitor the temperature and humidity parameters in real time and transmit the data to a temperature and humidity control system. The control system adjusts the spray volume of the spray system and the heating power of the heating device based on the monitoring data to maintain the pre-curing conditions. The pre-curing conditions are a temperature of 25℃ and humidity >90%, under which the hydration reaction of the cementitious material proceeds normally and moisture is not easily lost. The pre-curing time is 24 hours. During pre-curing, the spray system periodically sprays fine water droplets into the pre-curing chamber to increase air humidity. A drainage trough is located at the bottom of the pre-curing chamber to collect water droplets generated by the spray and excess water produced during curing, draining the chamber to prevent water accumulation from affecting the curing effect. After pre-curing, the side molds are removed from the mold using a demolding device, and then the slabs are removed from the lower mold to complete demolding. The demolded slabs are then transferred to a curing kiln for curing. Curing methods include ambient temperature wet curing for 7-28 days or steam curing for 12-24 hours. During ambient temperature wet curing, the humidity inside the curing kiln is maintained above 95%, allowing the slabs to undergo hydration and gradually develop strength at room temperature. During steam curing, the temperature inside the steam curing kiln is controlled at 60-80℃, the steam pressure at 0.1-0.3MPa, the steam humidity at 95%-100%, and the heating rate at 2-5℃ / min. Steam curing accelerates the hydration reaction of the cementitious materials, enabling the slabs to reach their design strength in a shorter time. After curing, the curing kiln is shut off from heating or steam supply, and the slabs are allowed to cool naturally to room temperature at a rate of 3-5℃ / min to prevent cracking due to uneven temperature stress caused by rapid cooling. After curing, the slabs are left in a natural environment for at least 24 hours for final curing to reduce the moisture content to <5%. After final curing, the compressive strength of the slabs should be no less than 3MPa, allowing for subsequent cutting, processing, and performance testing.
[0045] Further, in step 5, the water temperature is controlled at 15-25℃, the pH value is controlled at 7-9, the temperature of the foam slurry is controlled at 20-35℃ during stirring, and the water-to-solid ratio is controlled at 0.35-0.5. The water temperature is monitored by a temperature sensor and adjusted using a heating or cooling device to maintain it within the 15-25℃ range. The water pH value is monitored by a pH sensor and adjusted by adding an acidic or alkaline regulator to maintain it within the 7-9 range. If the pH value is too low, sodium hydroxide solution is added for adjustment; if the pH value is too high, citric acid solution is added for adjustment. Specifically, the preferred mass concentration of the sodium hydroxide solution is 1% to 3%, and the preferred mass concentration of the citric acid solution is 2% to 5%. Using low-concentration dilute solutions for slow dripping avoids drastic changes in local pH within the mixture, preventing sudden pH changes from damaging the chemical stability of the foaming agent. The foam slurry temperature is monitored in real-time by a temperature sensor and adjusted by regulating the stirring speed of the high-speed mixer or adding ice water or hot water to maintain it within the 20-35℃ range. The water-to-solid ratio is precisely controlled by a metering pump in the foam generator to maintain the ratio of water added to premixed powder mass within the range of 0.35-0.5.
[0046] Further, in step 7, the curing method can be either ambient temperature wet curing for 7-28 days or steam curing for 12-24 hours. After steam curing, the boards should be naturally cooled to room temperature at a rate of 3-5℃ / min. After curing, the boards should be placed in a natural environment for at least 24 hours for final curing to reduce the moisture content to <5%. When ambient temperature wet curing is chosen, the boards are placed in the curing kiln for 7-28 days, with water mist sprayed into the kiln daily to maintain humidity >95%. The curing kiln should also be equipped with insulation to maintain a stable temperature. When steam curing is chosen, the steam curing time is controlled at 12-24 hours. After steam curing, the steam valve is closed and the ventilation openings of the curing kiln are opened to allow the boards to cool naturally. During cooling, the cooling rate is controlled by adjusting the ventilation volume through a temperature and humidity control system to maintain it within the range of 3-5℃ / min. During final curing, the boards should be placed in a well-ventilated natural environment for at least 24 hours to allow moisture to gradually evaporate until the moisture content reduces to <5%. Example 2 This embodiment provides a second sintering preparation system and method, suitable for applications requiring higher product strength and high-temperature resistance. This process transforms coal-fired boiler slag into porous ceramic sound-absorbing panels through high-temperature sintering. Compared to the non-fired cementitious-foaming method in Example 1, the product exhibits higher strength and better durability.
[0047] Furthermore, the present application provides a preparation system for a coal slag-based high-porosity sound-absorbing board, which includes a raw material pretreatment unit, a batching and molding unit, a high-temperature sintering unit, and a post-treatment unit.
[0048] The raw material pretreatment unit is used to finely grind, remove iron, remove carbon, and dry the bottom ash of coal-fired boilers to obtain pretreated powder with stable composition. Specifically, the fine grinding mill in the raw material pretreatment unit is used to finely grind the boiler bottom ash to a particle size of <0.075mm, the iron removal device in the raw material pretreatment unit is used to remove ferromagnetic substances from the ash powder, the carbon removal device in the raw material pretreatment unit is used to reduce the carbon content in the ash powder, and the drying device in the raw material pretreatment unit is used to dry the ash powder to a moisture content of <2%.
[0049] The batching and molding unit is used to mix pretreated powder with flux, binder and foaming agent and then press it into shape; specifically, the batching bin and mixer in the batching and molding unit are used to mix the components according to the ratio to form a uniform mixture, the pressing and molding machine in the batching and molding unit is used to press the mixture into a molded blank with a specific shape, and the drying chamber in the batching and molding unit is used to dry the molded blank to a moisture content of <1%.
[0050] The high-temperature sintering unit is used to perform stepped heating sintering on the shaped green body to form a porous ceramic structure; specifically, the high-temperature sintering furnace in the high-temperature sintering unit is used to provide a high-temperature sintering environment and perform the stepped heating sintering process.
[0051] The post-processing unit is used to cut, grind, and surface-process the sintered porous ceramic slabs. Specifically, the cutting machine in the post-processing unit is used to cut the slabs to the required size, the grinding machine in the post-processing unit is used to grind and polish the surface of the slabs, and the surface processing device in the post-processing unit is used to perforate or groove the slabs.
[0052] The raw material pretreatment unit includes a fine grinding mill, an iron removal device, a decarbonization device, and a drying device. The fine grinding mill uses a ball mill or roller mill, with alumina balls or zirconium balls as the grinding media to avoid introducing iron impurities during the grinding process. The grinding is performed until the slag powder particle size is <0.075mm (200 mesh), and the specific surface area of the slag powder after fine grinding is 4000-6000cm² / g. The iron removal device uses a magnetic separator with a magnetic field strength of 0.3-0.5T to remove ferromagnetic substances from the slag powder. The decarbonization device uses a high-temperature roasting furnace, installed after the iron removal device. The roasting temperature is 300-500℃ to reduce the carbon content in the slag powder. Air or oxygen is introduced during roasting to ensure complete oxidation and combustion of the carbon. The drying device uses a belt dryer or rotary drum dryer, and the moisture content of the dried slag powder is <2%.
[0053] The batching and molding unit includes a batching silo, a mixer, a pressing and molding machine, and a drying chamber. The batching silos are used to store slag powder, flux, binder, and foaming agent. Feldspar or quartz is used as the flux to lower the sintering temperature and promote liquid phase formation; the amount of flux added is adjusted according to the chemical composition of the slag powder. Bentonite is used as the binder to improve the strength of the green body and promote densification during sintering; bentonite has a water absorption rate of 150%-300%. Carbon powder or calcium carbonate is used as the foaming agent to decompose and release gas during sintering, forming a porous structure. When carbon powder or calcium carbonate is selected as the foaming agent, the particle size must be controlled to be less than 0.075 mm. Fine particle size ensures uniform dispersion of the foaming agent in the mixture, avoiding excessively large through-hole defects caused by localized gas accumulation during high-temperature sintering, and preventing large bubble rupture leading to cracking of the green body. The mass ratio of each component is: slag powder 70%-80%, flux 5%-10%, binder 3%-5%, and foaming agent 2%-5%. A mixer is used to mix the components evenly. Water is added during mixing at 8%-12% of the total material mass, and the mixing time is 5-10 minutes. The moisture content of the resulting mixture is controlled at 10%-15%. A hydraulic or mechanical pressing machine is used, with a pressing pressure of 15-25 MPa, 1-3 pressing cycles, and a holding time of 30-60 seconds. After pressing, the dimensional accuracy of the green body is controlled within ±1 mm, and the density is 1.5-2.0 g / cm³. A drying chamber is used to dry the formed green body at 105℃ for 2-3 hours. The moisture content of the dried green body is <1%.
[0054] The high-temperature sintering unit includes a high-temperature sintering furnace and a temperature control system. The heating elements of the high-temperature sintering furnace are silicon carbide rods or molybdenum resistance wires, with a maximum operating temperature of 1200℃ to meet the temperature requirements of high-temperature sintering. The temperature control system uses an intelligent temperature controller with a temperature control accuracy of ±5℃ to ensure precise control of the sintering temperature. The sintering furnace is equipped with pushers or roller conveyors for transporting the billets; these pushers or roller conveyors are made of high-temperature resistant materials. The sintering atmosphere is either air or an inert gas, selected according to the product performance requirements. The sintering process adopts a stepped heating regime. Specifically, the heating rate from room temperature to 250℃ is 3℃ / min and held for 1 hour to remove residual moisture and organic impurities in the green body. The heating rate from 250℃ to 800℃ is 2℃ / min and held for 1 hour to allow the binder to decompose and the foaming agent to begin decomposing and releasing gas. The heating rate from 800℃ to 1100-1150℃ is 2℃ / min and held for 1-2 hours to complete liquid phase sintering and fix the pore structure. Finally, the green body is naturally cooled to room temperature at a cooling rate of 2-5℃ / min to avoid thermal stress cracking caused by excessively rapid cooling.
[0055] The post-processing unit includes a cutting machine, a grinding machine, and an inspection device. The cutting machine uses diamond cutting discs to cut the sintered sheets to the required dimensions, employing a diamond wire saw or waterjet cutting machine with a cutting accuracy of ±0.5mm. The grinding machine uses a belt grinder to polish the sheet surface, using coarse and fine sandpaper sequentially for rough and fine grinding, controlling the surface roughness to Ra=1.6-3.2μm. The inspection device includes a porosity meter, a sound absorption coefficient meter, and a compressive strength tester for performance testing of the finished product. The surface processing device is used to perforate or groove the finished sound-absorbing sheets. Perforation is done using laser drilling or mechanical punching, with a hole diameter of 5-15mm. Grooving uses V-grooves or rectangular grooves with a groove width of 2-5mm.
[0056] The method for preparing high-porosity sound-absorbing panels based on coal-fired boiler slag using the above-mentioned sintering method includes the following steps: The first step is raw material pretreatment. Boiler bottom ash is fed into a fine grinding mill via a feeding device and ground to a particle size <0.075mm. The fine grinding mill is either a ball mill or a roller mill, using alumina balls with a diameter of 10-30mm and a filling rate of 30%-40%, for a grinding time of 30-60 minutes. The specific surface area of the finely ground ash powder is 4000-6000 cm² / g. The finely ground ash powder is then passed through an iron removal device to remove ferromagnetic substances, followed by a carbon removal device to reduce the carbon content. The carbon removal device uses a high-temperature roasting furnace with a roasting temperature of 350-450℃ and a roasting time of 30-60 minutes, introducing air or oxygen to ensure complete oxidation and combustion of the carbon. The carbon-removed ash powder is then dried using a drying device to obtain boiler bottom ash powder with a particle size <0.075mm and a moisture content <2%.
[0057] The next step is batching and molding. Boiler bottom ash powder is added to the mixer according to the specified ratio using a metering device. Simultaneously, flux, binder, and foaming agent are added according to the same ratio, along with water at 8%-12% of the total material mass. The mixer is started and mixed for 5-10 minutes to form a homogeneous mixture. The mixture is then fed into a pressing and molding machine via a feeding device and pressed at 15-25 MPa for 1-3 cycles, with a holding time of 30-60 seconds, to obtain a molded blank. A release agent is applied to the mold surface during pressing to facilitate demolding.
[0058] The preferred release agent is zinc stearate powder or graphite emulsion aqueous solution, with the coating thickness controlled within the range of 0.1 mm to 0.2 mm. Zinc stearate powder or graphite emulsion aqueous solution not only ensures that the mixture does not stick to the mold under high pressure of 15-25 MPa, but also completely oxidizes and volatilizes during subsequent high-temperature sintering, leaving no harmful impurities inside the porous ceramic sound-absorbing panel.
[0059] Next, a high-temperature sintering step is performed. The formed green body is sent to a drying chamber for drying at 105℃ for 2-3 hours, resulting in a moisture content of <1%. The dried green body is then sent to a high-temperature sintering furnace for sintering using a stepped heating process: from room temperature to 250℃, the heating rate is 3℃ / min and held for 1 hour; from 250℃ to 800℃, the heating rate is 2℃ / min and held for 1 hour; from 800℃ to 1100-1150℃, the heating rate is 2℃ / min and held for 1-2 hours. Finally, it is allowed to cool naturally to room temperature to obtain a porous ceramic sound-absorbing panel. During sintering, the heating rate must be strictly controlled to prevent the rapid escape of gases released during the decomposition of the foaming agent, which could lead to large pores or defects. The sintering temperature is fine-tuned based on the chemical composition of the slag powder; a higher silica content results in a higher sintering temperature, while a higher calcium oxide content results in a lower sintering temperature.
[0060] The specific adjustment strategy is as follows: When the mass percentage of SiO2 in the pretreated slag powder is greater than 55%, the liquid phase viscosity of the sintering system is relatively high, and the upper limit of the maximum sintering temperature needs to be increased to 1150-1180℃ and the holding time extended to 2.5h; conversely, when the mass percentage of CaO is greater than 8% or the residual amount of Fe2O3 is greater than 5%, a large amount of low viscosity liquid phase is easily generated at high temperature. At this time, the maximum sintering temperature must be limited to 1050-1080℃ to prevent the porous structure from softening and collapsing or the closed-pore rate from increasing at high temperature.
[0061] Finally, post-processing steps are performed. The sintered porous ceramic sound-absorbing panels are cut to the required dimensions using a cutting machine. The surface is then polished using a grinding machine, with the surface roughness controlled at Ra=1.6-3.2μm. The finished sound-absorbing panels undergo surface treatment, including perforation or grooving. Perforation is performed using laser drilling or mechanical punching, with a perforation diameter of 5-15mm. Grooving uses V-grooves or rectangular grooves, with a groove width of 2-5mm.
[0062] After grinding and polishing, the surface of the porous ceramic sound-absorbing panel must be thoroughly cleaned with high-pressure air at a pressure of 0.4MPa to 0.6MPa, or the panel can be placed in an ultrasonic cleaning device for pure water cleaning and drying. This cleaning process thoroughly removes the dust that was forcibly squeezed into the surface pores during grinding, preventing dust from clogging the pores and preventing sound waves from entering the porous ceramic sound-absorbing panel, thus ensuring that the sound absorption coefficient meets the expected standard.
[0063] Although embodiments of this application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-porosity sound-absorbing panel based on coal slag, characterized in that, Includes the following steps: Step 1: Finely grind the bottom ash of the coal-fired boiler to obtain ash powder. Then, the ash powder is subjected to iron removal treatment to remove ferromagnetic substances and carbon removal treatment to reduce carbon content. The ash powder after carbon removal treatment is dried and then screened to obtain boiler bottom ash powder. Step 2: Mix the boiler bottom ash powder with functional additives to obtain a mixture; the functional additives include at least a foaming agent; Step 3: The mixture is molded to obtain a sheet blank; Step 4: The plate blank is cured to finally obtain the coal slag-based high-porosity sound-absorbing plate; wherein, during the molding or curing process, the foaming agent releases gas to form a porous structure inside the mixture.
2. The method for preparing a high-porosity sound-absorbing panel based on coal slag according to claim 1, characterized in that, In step one: the iron removal process is carried out using an iron removal device, and the magnetic field strength of the iron removal device is controlled at 0.3-0.5T; the carbon removal process is carried out using a carbon removal device, and the heat treatment temperature of the carbon removal device is controlled at 300-500℃.
3. The method for preparing a high-porosity sound-absorbing panel based on coal slag according to claim 1, characterized in that, In step two: the functional additive also includes a cementing material and a foam stabilizer; after the functional additive is mixed with the boiler bottom ash powder, the mass ratio of each component is: 60%-80% boiler bottom ash powder, 15%-25% cementing material, 0.1%-1.0% foaming agent, and 0.05%-0.2% foam stabilizer; the operation sequence of mixing the boiler bottom ash powder with the functional additive is: first add the boiler bottom ash powder and the cementing material for premixing, and then add the foaming agent and the foam stabilizer for mixing.
4. The method for preparing a high-porosity sound-absorbing panel based on coal slag according to claim 3, characterized in that, In step one: the bottom ash of the coal-fired boiler is fed into a crusher for coarse crushing, and then into a ball mill for fine grinding. The filling rate of the ball mill media is 30%-40%, and the specific surface area of the ash powder obtained after fine grinding is 3000-5000 cm² / g. The screening process is carried out using a multi-layer vibrating screen with screen apertures of 1 mm, 0.5 mm, and 0.15 mm respectively. The obtained boiler bottom ash powder has a particle size of 0.15-1 mm and a moisture content of less than 3%.
5. The method for preparing a high-porosity sound-absorbing panel based on coal slag according to claim 4, characterized in that, In step three: water is added to the mixture, and a high-speed mixer is started for high-speed mixing. The mixing speed of the high-speed mixer is 1000-1500 r / min, and the mixing time is 3-5 min, so that the mixture forms a foam slurry. The foam slurry is injected into the casting mold for the molding process. After casting, the mold is left to stand and foam to obtain the board blank. In step four: the curing process involves sending the board blank together with the casting mold into a pre-curing chamber for pre-curing. After pre-curing, the board blank is demolded and transferred to a curing kiln for curing. After curing, the board blank is allowed to cool naturally.
6. The method for preparing a high-porosity sound-absorbing panel based on coal slag according to claim 5, characterized in that, In step three: the temperature of the added water is controlled at 15-25℃, the pH value of the added water is controlled at 7-9, the temperature of the foam slurry is controlled at 20-35℃ during the high-speed stirring process, and the water-to-solid ratio of the added water to the mixture is controlled at 0.35-0.5; In step four: the pre-curing conditions are a temperature of 25℃ and a humidity greater than 90%, and the pre-curing time is 24h; when steam curing is carried out in the curing kiln, the steam pressure is controlled at 0.1-0.3MPa, the steam humidity is controlled at 95%-100%, and the heating rate is controlled at 2-5℃ / min.
7. The method for preparing a high-porosity sound-absorbing panel based on coal slag according to claim 1, characterized in that, In step one: the bottom ash of the coal-fired boiler is fed into a fine grinding mill for fine grinding until the particle size of the ash powder is less than 0.075 mm, and the specific surface area of the ash powder obtained after fine grinding is 4000-6000 cm² / g; the moisture content of the ash powder after drying is less than 2%; In step two: the functional additive also includes a flux and a binder; after the functional additive is mixed with the boiler bottom ash powder, the mass ratio of each component is: 70%-80% boiler bottom ash powder, 5%-10% flux, 3%-5% binder, and 2%-5% foaming agent.
8. The method for preparing a high-porosity sound-absorbing panel based on coal slag according to claim 7, characterized in that, In step three: water is added to the mixture, and the mixture after adding water is fed into a pressing and molding machine through a feeding device for pressing and molding. The pressing pressure is 15-25 MPa, the pressing number is 1-3 times, and the holding time is 30-60 s to obtain the plate blank. In step four: the curing treatment includes sending the plate blank into a drying chamber for drying, and then sending the dried plate blank into a high-temperature sintering furnace for sintering. The sintering process adopts a stepped heating regime: the heating rate from room temperature to 250℃ is 3℃ / min and held for 1 hour, the heating rate from 250℃ to 800℃ is 2℃ / min and held for 1 hour, the heating rate from 800℃ to 1100-1150℃ is 2℃ / min and held for 1-2 hours, and finally it is naturally cooled to room temperature at a cooling rate of 2-5℃ / min.
9. A system for a high-porosity sound-absorbing panel based on coal slag, characterized in that, A method for preparing a coal ash-based high-porosity sound-absorbing panel as described in any one of claims 1 to 8 includes a raw material pretreatment unit, a batching and mixing unit, a foaming and molding unit, and a curing and solidification unit connected in sequence. The raw material pretreatment unit receives the bottom ash from a coal-fired boiler and outputs the treated boiler bottom ash powder. The batching and mixing unit receives the boiler bottom ash powder and mixes it with the functional additive, outputting the mixture. The foaming and molding unit receives the mixture and generates the porous structure within the mixture, molding and outputting the panel blank. The curing and solidification unit receives the panel blank and performs the curing treatment on the panel blank, outputting the coal ash-based high-porosity sound-absorbing panel.
10. The preparation system for a coal slag-based high-porosity sound-absorbing panel according to claim 9, characterized in that, The raw material pretreatment unit includes an iron removal device, a carbon removal device, and a drying device; the iron removal device is installed before the drying device, and the magnetic field strength of the iron removal device is 0.3-0.5T; the carbon removal device is installed after the iron removal device, and the heat treatment temperature of the carbon removal device is controlled at 300-500℃.
